2019
DOI: 10.1016/j.foodcont.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol in cereal-based baby food production process. A review

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Deoxynivalenol, also denoted as vomitoxin, is produced by fungi of the Fusarium genus, mainly by Fusarium graminearum and F. culmorum, which are both associated with FHB disease (Fusarium head blight) in cereals, especially oats, barley, wheat rye, and maize, and less frequently in rice, sorghum, and triticale [17,146]; it also contaminated cereal-derived food products such as bread, pasta, or beer. DON is the predominant trichothecene all over the world, although it is among the least toxic of the trichothecenes, and its occurrence is considered to be an indicator of the potential presence of other, more toxic trichothecenes [53].…”
Section: Trichothecenes Type B (Deoxynivalenol)mentioning
confidence: 99%
See 1 more Smart Citation
“…Deoxynivalenol, also denoted as vomitoxin, is produced by fungi of the Fusarium genus, mainly by Fusarium graminearum and F. culmorum, which are both associated with FHB disease (Fusarium head blight) in cereals, especially oats, barley, wheat rye, and maize, and less frequently in rice, sorghum, and triticale [17,146]; it also contaminated cereal-derived food products such as bread, pasta, or beer. DON is the predominant trichothecene all over the world, although it is among the least toxic of the trichothecenes, and its occurrence is considered to be an indicator of the potential presence of other, more toxic trichothecenes [53].…”
Section: Trichothecenes Type B (Deoxynivalenol)mentioning
confidence: 99%
“…The maximum level of DON of 200 µg/kg was set by the EU in cereal-based baby foods for infants and young children, as well as levels of 750 µg/kg in flour and 500 µg/kg in breads [146]. At high temperatures, DON is a very stable trichothecene (120 • C, moderately stable at 180 • C), as well as soluble in water and in polar solvents such as aqueous methanol, acetonitrile, and ethyl acetate [148], and it is found during the storage and processing of products [100].…”
Section: Trichothecenes Type B (Deoxynivalenol)mentioning
confidence: 99%
“…(right ear (thickness at 24 h − thickness at 0 h)) − (left ear (thickness at 24 h − thickness at 0 h)) = DTH (µm) (2) The measurements were performed in randomized order and blinded.…”
Section: Vaccine-specific Immunoglobulins (Igs) In Serummentioning
confidence: 99%
“…The mycotoxin deoxynivalenol (DON) is a highly prevalent food contaminant, known to induce immunotoxicity in humans and animals. DON is produced as a secondary metabolite from Fusarium fungus species, which contaminates human food at a global level, especially cereal and grain-based products [ 1 , 2 ]. Acute and chronic exposure to DON have significant negative impact on intestinal, neurological and reproductive systems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies from different geographical regions have shown that pregnant women and newborns are highly exposed to different mycotoxins (2). Deoxynivalenol (DON), a trichothecene mycotoxin produced by different Fusarium fungi species, is one of the most prevalent mycotoxins occurring in human food (12). DON exhibits intestinal, neurological, reproductive and immunotoxicity (13).…”
Section: Introductionmentioning
confidence: 99%